Designing the Requirements of the Digital Health Literacy System Focusing on Cancer - Fatemeh Mirshekari; Elham Maserat (پیاورد سلامت)
Background and Aim:  Considering the growing trend of cancer in Iran, the development and implementation of digital health literacy systems accelerates the capabilities of digital health and the self-management process of patients. Digital health literacy means the ability to effectively and consciously use digital technologies to access health-related information and services. This skill plays an important role in accessing medical information, disease management, improving the quality of life of people, especially cancer patients. Digital health literacy is considered as one of the most key factors of equal access to digital health information. The purpose of the present study was to formulate the requirements of the digital health literacy system with a focus on cancer. Materials and Methods: The present study was conducted in two phases of literature review and validity and reliability of requirements in 2023. In the first stage, a literature review was conducted with the keywords of digital health literacy, cancer, requirements, system and application in databases such as PubMed, Scopus, Google Scholar, academic Jihad scientific database and specialized websites. To check the content validity of the survey, 62 experts were surveyed and CVI and CVR were calculated. Results: Hundered and twenty seven functional and non-functional components were approved. Requirements in the functional section was divided in six main dimensions information literacy module (8 functional components), information and communication technology literacy module (18 functional components), media literacy (5 functional components), public, specialized and population-oriented health literacy module (47 functional components) ), digital health literacy module (28 functional components), and digital health literacy module in cancer (6 functional components) were divided. In the section of digital health literacy in cancer, the main components of needs assessment, digital health literacy training, evaluation and monitoring of the effectiveness of digital interventions and information search skills were approved. Fifteen non-functional components were also approved. Cronbach’s alpha coefficient obtained (92%) indicated high reliability and reproducibility. Conclusion: Digital health literacy systems can facilitate health care services. Considering the acceptable validity and reliability of the study, the defined requirements can be used to implement digital health literacy systems centered on cancer.